Data fusion strategy for quantitative analysis of n-3 fatty acids in commercial krill oil - Ahmmed, F. (2020)
Raman and attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy were used to analyse seven krill oil capsules and twenty-five calibration samples to quantitate astaxanthin, EPA plus DHA and other important fatty acids. Spectroscopic data was calibrated against FAME profiles (measured by GC-MS) and astaxanthin concentrations (measured by UV-VIS). Raman spectra was found to be suitable to quantify astaxanthin, EPA, DHA and EPA + DHA, with reasonable root mean square error of prediction (RMSEP) for test set validation: 40 μg g-1, 2.5%, 2.2% and 4.5% respectively.